2002
DOI: 10.1300/j072v03n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Prohexadione-Calcium Controls Vegetative Shoot Growth in Apple

Abstract: Prohexadione-calcium (Phd-Ca) (BAS 125W or 9054 W) applied at petal fall (PF) or within 10 days of PF to apple trees as a single spray or as multiple low-rate sprays reduced the current season's shoot growth. Sprays applied 2 to 3 weeks after PF were less effective. Timing of the initial spray was more important than rate in achieving early growth suppression, but rate was most important for maximum season-long growth control. Reduced shoot growth enhanced spray coverage and reduced dormant pruning time by as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 17 publications
(14 reference statements)
6
33
1
5
Order By: Relevance
“…No entanto, a intensificação dos trabalhos de poda, para restringir o desenvolvimento vegetativo das plantas, pode aumentar os custos de produção no manejo da pereira. Por isso, o controle do desenvolvimento vegetativo por meios químicos pode ajudar a reduzir o crescimento excessivo, limitar o tamanho das plantas ou restringir o crescimento em determinado momento, o que permite melhor equilíbrio entre o desenvolvimento vegetativo e a frutificação (Miller, 2002).…”
Section: Introductionunclassified
“…No entanto, a intensificação dos trabalhos de poda, para restringir o desenvolvimento vegetativo das plantas, pode aumentar os custos de produção no manejo da pereira. Por isso, o controle do desenvolvimento vegetativo por meios químicos pode ajudar a reduzir o crescimento excessivo, limitar o tamanho das plantas ou restringir o crescimento em determinado momento, o que permite melhor equilíbrio entre o desenvolvimento vegetativo e a frutificação (Miller, 2002).…”
Section: Introductionunclassified
“…그러나 200mg・L -1 농도에서 신초생장이 과도하게 억제되고 과실비대 및 품질이 감소되 었다는 보고 (Basak and Rademacher, 2000)가 있는가 하면 250mg・L -1 농도로 살포해도 M.106 및 M.111 대목에 접목한 사과나무에서는 신초생장 억제효과가 없었다는 보고 (Miller, 2002)도 있는 등 연구자에 따라 결과의 차이가 크게 보고되 고 있다.…”
unclassified
“…Treatment with Pro-Ca reduced shoot length by 21-71% in apples depending on the dose, timing of treatment and cultivar (Miller 2002). Similar effects were observed in 'Smoothee Golden Delicious' (Medjdoub et al 2004), 'Empire' (Cline et al 2008), and'Royal Gala' and'Fuji' (Mata et al 2006) apple trees.…”
Section: Discussionmentioning
confidence: 69%
“…While Medjdoub et al (2005) and Greene (2008) have reported that Pro-Ca increases fruit set, other researchers explained it as ineffective (Costa et al 2000;Miller 2002). In the present study, Pro-Ca has no significant influence on fruit set compared to control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation